2019
DOI: 10.3389/fimmu.2019.00701
|View full text |Cite
|
Sign up to set email alerts
|

NET Formation in Bullous Pemphigoid Patients With Relapse Is Modulated by IL-17 and IL-23 Interplay

Abstract: Background: DNA extracellular traps (ETs), released by neutrophils (NETs), or eosinophils (EETs), play a pathogenic role in several autoimmune disorders. However, to date, NETs have never been investigated in bullous pemphigoid (BP) with respect to clinical and immunological activities, both at baseline and at time of relapse which have been characterized with specific IL-17 and IL-23 patterns. Objective: We sought to assess whether ETs were associated with BP as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 68 publications
(85 reference statements)
3
44
0
1
Order By: Relevance
“…Meanwhile, NLRP3 mRNA expression was enhanced in response to IL-17 but not in response to IL-23 suggesting that IL-1β expression could also be regulated in an inflammasome-independent manner as recently highlighted in an experimental caspase-1/11-deficient mouse model of epidermolysis bullosa acquisita (29). We already highlighted discrepancies in the effects of IL-17 and IL-23 in a recent study showing that IL-23 was a more potent inductor of NETosis than IL-17 in BP (30). Release of immunomodulatory cytokines and chemokines during this process could play a role either in favoring the auto-immunity or the auto-inflammatory processes.…”
Section: Discussionmentioning
confidence: 88%
“…Meanwhile, NLRP3 mRNA expression was enhanced in response to IL-17 but not in response to IL-23 suggesting that IL-1β expression could also be regulated in an inflammasome-independent manner as recently highlighted in an experimental caspase-1/11-deficient mouse model of epidermolysis bullosa acquisita (29). We already highlighted discrepancies in the effects of IL-17 and IL-23 in a recent study showing that IL-23 was a more potent inductor of NETosis than IL-17 in BP (30). Release of immunomodulatory cytokines and chemokines during this process could play a role either in favoring the auto-immunity or the auto-inflammatory processes.…”
Section: Discussionmentioning
confidence: 88%
“…To measure morphological changes during the early phase of the NETotic process, we performed DANA, as described before (39). DANA-based analysis of NAE in exposed PMN is accepted as an indicator of early NETs formation process as demonstrated previously (19,48,49). In this study, we used DANA to better characterize interactions of PMN and T. b. brucei trypomastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…These observations make eosinophils interesting targets for therapy 91 . A recent study reported the presence of NETs at sites of blister formation in BP that decreased with time following treatment in patients undergoing remission 92 .…”
Section: Eets and Nets In Bullous Pemphigoidmentioning
confidence: 99%